Feather corticosterone reveals effect of moulting conditions in the autumn on subsequent reproductive output and survival in an Arctic migratory bird - Harms, N.J. (N. Jane); Legagneux, P. (Pierre); Gilchrist, H.G. (Hugh Grant); Bêty, J. (Joël); Love, O.P. (Oliver P.); Forbes, M. (Mark); Bortolotti, G.R. (Gary R.); Soos, C. (Catherine) (Proceedings of the Royal Society B: Biological Sciences, 2014)
For birds, unpredictable environments during the energetically stressful times of moulting and breeding are expected to have negative fitness effects. Detecting those effects however, might be difficu